(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Energy assumes an essential job in the economic development. Energy being rare, it turns into a vital factor underway. In the event that we take a gander at Gujarat from the earliest starting point of industrialization it has been a noteworthy benefactor in the industrial yield. Starting at now it has 11 of Indian industries, utilizes 21 of aggregate material accessible in India, expends around 15 of the energy and adds to over 18 in the aggregate value included of India’s industrial GDP. There appears to be high relationship between’s energy consumption and industrial yield. This investigation is an endeavor to comprehend the pattern on energy consumption and industrial yield for the period 1999-2015 utilizing straightforward relationship and relapse work.